Hedge Fund Stock Trading in the Financial Crisis of 2007–2009 - Ben-David, Itzhak; Franzoni, Francesco; Moussawi, Rabih (Review of Financial Studies, 2012)
Hedge funds significantly reduced their equity holdings during the recent financial crisis. In 2008:Q3––Q4, hedge funds sold about 29% of their aggregate portfolio. Redemptions and margin calls were the primary drivers of selloffs. Consistent with forced deleveraging, the selloffs took place in volatile and liquid stocks. In comparison, redemptions and stock sales for mutual funds were not as severe. We show that hedge fund investors withdraw capital three times as intensely as mutual fund investors do in response to poor returns. We relate this stronger sensitivity to losses to share liquidity restrictions and institutional ownership in hedge funds.